2015
DOI: 10.1039/c5cp03945b
|View full text |Cite
|
Sign up to set email alerts
|

Exponential size-dependent tunability of strain on the transport behavior in ZnO tunnel junctions: an ab initio study

Abstract: It is an interesting issue if the transport behavior of a piezoelectric tunnel junction is sensitive to external strain or stress, and it implies a prospect for developing novel mechanical sensors, transducers, piezotronic devices, etc. Many studies paid attention to this issue, yet how the strain and stress tunable transport behavior of a tunnel junction depends on the barrier thickness is still rarely known. Using the first principles calculations, we investigate the size-dependent and strain-tunable transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The tunneling effect can also be altered. Simulations by Zheng et al revealed that external strain can effectively tune the transport properties of ZnO piezoelectric tunnel junctions, and the size dependence of the strain tunability exhibits a simple exponential law [ 145 ].…”
Section: Piezotronics Based On Zno Nanowiresmentioning
confidence: 99%
“…The tunneling effect can also be altered. Simulations by Zheng et al revealed that external strain can effectively tune the transport properties of ZnO piezoelectric tunnel junctions, and the size dependence of the strain tunability exhibits a simple exponential law [ 145 ].…”
Section: Piezotronics Based On Zno Nanowiresmentioning
confidence: 99%
“…A direct and powerful control of tunnel junctions is via strain. In fact, it is a natural idea to control the tunnel conductance of PTJs via the piezoelectric effect [1,2,[42][43][44]. Since enhanced piezoelectric properties are forecast when the size of the piezoelectric material is down to the nanoscale, people are eager to control their new functionalities in novel functional nanoelectronics.…”
Section: Strain In Tunnel Junctionsmentioning
confidence: 99%
“…Combining the strain effect with other influencing factors such as electrodes [93,94] and size effect [42], one can gain a more comprehensive picture of the strain controllability on the performances of ZnO piezoelectric nanodevices, as reported by research based on ab initio calculations. For example, Zhu et al [42] reported size-dependent amplification of tunnel conductance through ZnO tunnel junctions by strain reversal. The ratio of tunnel conductance under 3% strain G + ( ) to that under −3% strain G ,…”
Section: Strain-tunable Transport Behavior In Zno Tunnel Junctionsmentioning
confidence: 99%
See 1 more Smart Citation